2016
DOI: 10.1038/srep23319
|View full text |Cite
|
Sign up to set email alerts
|

A p-i-n junction diode based on locally doped carbon nanotube network

Abstract: A p-i-n junction diode constructed by the locally doped network of single-walled carbon nanotubes (SWNTs) was investigated. In this diode, the two opposite ends of the SWNT-network channel were selectively doped by triethyloxonium hexachloroantimonate (OA) and polyethylenimine (PEI) to obtain the air-stable p- and n-type SWNTs respectively while the central area of the SWNT-network remained intrinsic state, resulting in the formation of a p-i-n junction with a strong built-in electronic field in the SWNTs. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Another way to generate nonlinearity may be to selectively dope the channels of SWNT networks with triethyl oxonium hexachloroantimonate and polyethylenimine to form p-i-n junctions with strong builtin electric fields. Using this method, high-performance diodes with a high rectification ratio, large forward current, and low reverse saturation current have been realized [25], and the I-V characteristics show clear nonlinear rectifying properties. An asymmetric contact was found to effectively improve p-i-n diode performance [26].…”
Section: Electric Nonlinearity Of Individual Cnt and Cnt Complexed Wi...mentioning
confidence: 99%
“…Another way to generate nonlinearity may be to selectively dope the channels of SWNT networks with triethyl oxonium hexachloroantimonate and polyethylenimine to form p-i-n junctions with strong builtin electric fields. Using this method, high-performance diodes with a high rectification ratio, large forward current, and low reverse saturation current have been realized [25], and the I-V characteristics show clear nonlinear rectifying properties. An asymmetric contact was found to effectively improve p-i-n diode performance [26].…”
Section: Electric Nonlinearity Of Individual Cnt and Cnt Complexed Wi...mentioning
confidence: 99%
“…They also have fully saturated surface bonds and no interface states. [11][12][13][14][15][16][17][18] If these materials can be used to collaboratively construct diodes, then their respective advantages can be fully utilized to achieve high device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Diversied junctions have been used to form built-in electric elds for fabricating diodes based on the BP or carbon materials including p-n junction, heterojunction, and Schottky junction. 5,8,13,[17][18][19][20][21] We previously investigated a p-i-n junction diode based on locally-doped individual SWCNTs or an SWCNT network. This led to a rectication ratio of 10 4 and an ideal factor of 1.3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not easy to find a flexible material possessing both p- and n-type TE properties . Only a few joint-free flexible TE devices have been reported, which are mainly fabricated with carbon nanotubes (CNTs) and their composites. Xie et al reported compact-designed flexible TE modules with CNT films doped by drop-casting polyethylenimine solution . Kim et al reported a CNT fiber-based TE generator formed by brushing the solution of p- and n-type dopants on the CNT fiber …”
mentioning
confidence: 99%